A fault tolerant control scheme for the reentry vehicle with reduced control effort. Issue 24 (2018) - Chang, Jing; Guo, Zongyi; Cieslak, Jérôme
Abstract: An active fault-tolerant control scheme is proposed in this paper for Hypersonic Reentry Vehicle (HRV) which subjected to actuator faults. Disturbance observer based compensation idea is incorporated with a fault/uncertainty effect-triggered control approach to deal with vehicle attitude tracking problem with unmatched uncertainties and actuator faults. First, an improved adaptive disturbance observer (ADO) is introduced to estimate the lumped uncertainties and actuator faults, which transforms the uncertain system to a matched structure. With the estimated lumped disturbance (uncertainties and actuator faults) from the observer, the control law is given based on the combination of back-stepping based techniques and sliding-mode algorithm. The proposed scheme can achieve robust tracking performance with reduced control effort by eliminating the detrimental uncertainty and actuator fault while keeping the beneficial uncertainty and actuator fault. Simulation results obtained on the reentry vehicle have demonstrated the effectiveness of the approach proposed.